The Relationship Between Posttraumatic Growth and Psychosocial Variables in Survivors of State Terrorism and Their Relatives - Cárdenas-Castro, Manuel (Journal of interpersonal violence, 2021)
The present study explores reports of growth in survivors and family members of victims of state terrorism (N = 254) in Chile from 1973 to 1990. The results indicate the presence of reports of posttraumatic growth (M = 4.69) and a positive and statistically significant correlation with variables related to the life impact of the stressful events (r = .46), social sharing of emotions (r = .32), deliberate rumination (r = .37), positive reappraisal (r = .35), reconciliation (r = .39), spiritual practices (r = .33), and meaning in life (r = .51). The relationship between growth and forgiveness is not statistically significant. The variables that best predict posttraumatic growth are positive reappraisal (β = .28), life impact (β = .24), meaning in life β = .23), and reconciliation (β = .20). The forward-method hierarchical model indicates that these variables are significant predictors of growth levels, R2 = .53, F(8, 210) = 30.08, p < .001. The results indicate that a large proportion of the victims of state terrorism manage to grow after these experiences, and the redefinition of meaning in life and the positive reappraisal of the traumatic experiences are the elements that make it possible to create a new narrative about the past.